Herrerías Guerra. L. (1996). Espero estar en la verdad. La búsqueda ontológica de Paul Ricœur. Roma: Editrice Pontificia Universitá Gregoriana. ISBN: 88-7652-708-7. Número de páginas: 287. - Zapata S.J., Guillermo (2005)
null